Pengaruh Financial Attitude, Financial Knowledge, Dan Financial Behavior Terhadap Financial Technology Literacy - Jefrie Jefrie; Hendra Wiyanto (Jurnal Manajerial Dan Kewirausahaan, 2020)
The purpose of this research is to analyze  the effect of Financial Attitude, Financial Knowledge, and Financial Behavior toward Financial Technology Literacy. The sample of this research were Go-Pay users in West Jakarta. The sample was selected using a non-probability sampling method amounted to 250 respondents by distributing questionnaire via online through the Google form section. The data analysis technique used is structural equation modeling that helped by Smart-PLS version 3.0 program. The results of this research reveals that Financial Attitude, Financial Knowledge, and Financial Behavior have effects towards Financial Technology Literacy on Go-Pay users in West Jakarta. Tujuan dari penelitian ini adalah untuk menguji pengaruh Financial Attitude, Financial Knowledge, dan Financial Behavior terhadap Financial Technology Literacy. Sampel pada penelitian ini adalah pengguna Go-Pay di Jakarta Barat. Sampel dipilih dengan menggunakan metode non probability sampling yang berjumlah sebanyak 250 responden dengan menyebarkan kuesioner secara online dengan bantuan Google form. Teknik analisis data yang digunakan adalah structural equation modeling yang dibantu dengan bantuan program Smart-PLS versi 3.0. Hasil yang didapat pada penelitian ini menunjukkan bahwa terdapat pengaruh Financial Attitude, Financial Knowledge, dan Financial Behavior terhadap Financial Technology Literacy pada pengguna Go-Pay di Jakarta Barat.